Formação de professores e práticas pedagógicas para o ensino de história em contexto pluriétnico no Alto Rio Negro - Silva, Letícia Alves da (2017)
The present dissertation entitled "Teacher training and pedagogical practices for the teaching of History in a multi-ethnic context in the High Rio Negro river region", is a contribution in the discussions about Pedagogical Practices directed to the History teaching focused in the ethnic, linguistic and culturally diversified indigenous populations. We will start from the different historical and pedagogical approaches related to the History teaching, with the purpose of thinking reflexively about the strategy and the meeting of the alterities. Simultaneously, we try to follow the paths of the construction of the idea of multiculturality and interculturality, that grounds the History teaching in the multi-ethnic context. We will try to demonstrate that multiculturalism and interculturality will be connected to the History teaching and overlapped in the pedagogical process, in order to make possible the pluriethnic understanding of the reality in the indigenous and non-indigenous schools. This objectifies the structuring of pedagogical practices in favor of school education that promotes relationship between the different cultures through the articulation of the indigenous and non-indigenous knowledge. Therefore, Amazonic region, strictly the High Rio Negro river region, presents complex relationships of different cultures, thus becoming fertile soil to think about the History teaching, in this intercultural context. We exemplify this quest Introducing the problem of absence of teacher training, to develop learning methods that unites the indigenous knowledge to the History contents, and that works this. The theme is contextualized with the ethnic, linguistic and sociocultural diversity of the indigenous students that annually join the Municipal, State and Federal education establishments of São Gabriel da Cachoeira City. We seek to reach the main objective developing a teacher‘s workshop which was attended by 33 indigenous teachers who work in Federal, State and Municipal basic education at the High Rio Negro river region. The workshop must develop new pedagogical practices inside a multi-ethnic context in the High Rio Negro river region. To the development of this workshop we chose the active-research method, because it possibilities the intervention in the History teaching praxis and its improvement. Involvement of researchers and respondents was essential for evaluate the problem in vogue, making it dialog with the reality and its interpretation. Thus, the effectuation of the workshop of the pedagogical practices for History teaching in a multi-ethnic context, allowed the articulation of the ethnic knowledge with the contents of the History curriculum of basic education, thus contributing to the improvement of the understanding, interpretation and contextualization of the environment of the indigenous student.